Determinants of dementia risk among older adults with probable sarcopenia and sarcopenia - Nur Indrawaty Lipoeto; Divya Vanoh; Desmawati Desmawati; Wan Rosli Wan Ishak; Rosminah Mohamed (BMC Public Health)
Abstract Background Probable sarcopenia is a condition related to low muscle strength which increases the risk of sarcopenia. Both probable sarcopenia and sarcopenia increases the risk of dementia. The aim of this study is to investigate the factors associated with dementia among probable sarcopenia and sarcopenia older adults. It was hypothesized that comorbidities among probable sarcopenia and sarcopenia subjects may elevate the risk of dementia. Methodology This study involved 194 older adults with probable sarcopenia and sarcopenia aged 60 years and above. Sarcopenia was assessed using the Asian Working Group of Sarcopenia (AWGS) 2019. Among the parameters investigated in this study were sociodemographic, medical history, anthropometry, body composition, physical fitness, subjective cognitive decline, depressive symptoms, cognitive function and functional status. Dementia risk was assessed using the Montreal Cognitive Assessment (MoCA) tool. Adjusted binary logistic regression was employed to identify the factors associated with dementia among probable sarcopenia and sarcopenia older adults. Results Probable sarcopenia subjects with dementia were older (68.5(7.8) years old) as compared to those without dementia (66.0(6.0) years old). Among the probable sarcopenia, 66.1% of the subjects with dementia had hypertension, while 64.3% of the sarcopenia subjects had hypertension. Fat mass was significantly higher among dementia subjects with probable sarcopenia (33.0(6.5) %) as compared to non-dementia subjects (30.4(6.8) %). Multivariate analysis revealed that hypertension (OR: 4.049; 95% CI: 1.510; 10.855, p = 0.005) was the only factor associated with dementia risk among older adults with probable sarcopenia and sarcopenia. Conclusion Hypertension is the only factors associated with risk of dementia after adjusting for potential confounders among older adults with probable sarcopenia and sarcopenia. Good control of blood pressure is essential among sarcopenia patients for lowering risk of dementia. Well-designed clinical trials are essential to investigate optimizing blood pressure level to reduce risk of dementia among patients with sarcopenia and probable sarcopenia.